2020
DOI: 10.3390/w12051443
|View full text |Cite
|
Sign up to set email alerts
|

Hydrochemical Characteristic of Groundwater and Its Impact on Crop Yields in the Baojixia Irrigation Area, China

Abstract: While irrigated crops produce much higher yields than rain-fed crops, the ionic components of irrigation water have important effects on crop yield. Groundwater is widely used for irrigation in the Baojixia irrigation area in China. The chemical characteristics and water quality of groundwater in the Baojixia irrigation area were analyzed and evaluated to study the impact of groundwater quality on crop yield. Results showed cations in the groundwater to mainly be Na+, Ca2+, and Mg2+, whereas the anions are mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Electrical conductivity is essential for the assessment of the water quality of a particular area. It acts as a baseline for measuring other water quality parameters as conductivity measures dissolved ionic concentration 46 . A significant variation in the conductivity value indicates a change in water quality or inclusion of some contaminants or indicates that the area is affected by some source of pollution 47 .…”
Section: Resultsmentioning
confidence: 99%
“…Electrical conductivity is essential for the assessment of the water quality of a particular area. It acts as a baseline for measuring other water quality parameters as conductivity measures dissolved ionic concentration 46 . A significant variation in the conductivity value indicates a change in water quality or inclusion of some contaminants or indicates that the area is affected by some source of pollution 47 .…”
Section: Resultsmentioning
confidence: 99%
“…Combining the analysis results, it can be concluded that the main reason for the change in water quality at the sampling point is that agriculture or mining activities lead to the increase of nitrate concentration in the area, so the water quality index is low. In addition, the oxidation and leaching process of pyrite and coal clean waste will also affect the chemical properties of the diving groundwater [ 7 , 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is the concentration of sodium relative to calcium and magnesium. Calculated according to the following standard formula [ 7 , 39 ]: …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrical Conductivity is essential for the assessment of the water quality of a particular area. It acts as a baseline for measuring other water quality parameters as conductivity measures dissolved ionic concentration (Feng et al 2020). A significant variation in the conductivity value indicates a change in water quality or inclusion of some contaminants or indicates that the area is affected by some source of pollution (Dawson et al 2019).…”
Section: Analysis Of Groundwater Quality Parametersmentioning
confidence: 99%